Analisis Pengaruh Model Pembelajaran Examples Non Examples Terhadap Hasil Belajar Siswa Pada Kompetensi Dasar Tata Ruang Kantor (Studi Pada Siswa Kelas X OTKP SMK Pawiyatan Surabaya) - Nia Kurniawati; Novi Trisnawati (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of writing this article is to describe the effect of the Example Non Examples learning model on student learning outcomes on the basic competency of office layout in class X OTKP SMK Pawiyatan Surabaya. The research sample of Class X OTKP 3 (experimental class) with Example Non Example method and Class X OTKP 2 (control class) is subject to conventional learning models, with the number of students in each class of 30 students. This type of research is a literature study. The results showed that the office spatial learning materials have used learning models that prioritize group learning activities to study the material. Examples of learning are not examples that can make students become more understanding of the material being studied than students who successfully analyze the images presented. In addition, non-example model examples can make students find themselves understanding the results of the analysis conducted, make the classroom learning process in which students become active participants rather than passive observers, and are responsible for their learning. based on the research that has been done, the suggestion that can be conveyed is to use the Cooperative learning model Project Based Learning type is expected to provide one of the variations of learning models on the basic competencies of office layout.